Normative Provision of the Right to Liberty and Integrity of the Person in the Light of International and National Legislation - V. V. Ablamska (Bulletin of Kharkiv National University of Internal Affairs)
The normative provision of the right to liberty and integrity of the person in the light of international and national legislation has been studied. The provisions of generally recognized international legal acts guaranteeing the right to liberty and integrity of the person have been provided. At the same time, there are also convention regulations, which provide cases of possible restriction of the researched right, and we note that such a right is not absolute in this regard. It has been determined that the norms of the Constitution of Ukraine, which regulate the right to liberty and integrity of the person, comply with international legal acts.